A PRESENÇA DA MÍDIA NO COTIDIANO DOS PEQUENOS PRODUTORES RURAIS EM PONTA GROSSA/PR: possíveis relações de apropriação da produção midiática na agricultura familiar 2007 - Oliveira, João Carlos Dias de (2007)
This study has as objective to verify if the familiar farmings of Ponta Grossa (Pr) use the means of mass communication as a tool when searching for useful information for their productive activities. In this way, it has been made interviews using research forms with 60 producers from small rural communities that fit in the conceptual characteristics of familiar agriculture. As the object of the study is inserted in the relationship between the media chanells and the producer, were also analyzed productions related to rural communication by radio, newspaper, and television, besides a poll, using forms with radio stations in Ponta Grossa. The methodology used was the quantitative and qualitative empirical investigation, and also documental researches and oral interviews. Theoretical reflections are supported by authors that discuss the communication, from its importance and its relationships between emission and reception of the media messages. The perspectives in the general study pointed out the importance of the communication that takes place into the social processes. The particular basis presents a critical analyzes of the production of the channels directed at rural places and an understanding of the audience that receives the messages. For a better knowledge of the object of the study, the bibliographic researches presents a historical formation, a present conjuncture and a conception of familiar agriculture, either as in national terms as in a particular character of the county. The results certify that the studied public has access to the main media channels and knows about the most popular forms of production in this field. Nevertheless, the use of media as a tool in their rural activity is not a current practice between them.